Ab initio phase stability and electronic conductivity of the doped-Li4Ti5O12 anode for Li-ion batteries. (15th August 2019) - Tsai, Ping-chun; Nasara, Ralph Nicolai; Shen, Yu-chen; Liang, Chih-chao; Chang, You-wen; Hsu, Wen-Dung; Thuy Tran, Ngoc Thanh; Lin, Shih-kang
Abstract: The Li4 Ti5 O12 (LTO) defect spinel is known for its excellent durability of "10, 000" cycle counts and high level of safety as an anode material in lithium-ion batteries, but it shows an intrinsic insulating property and poor electrochemical kinetics. Doping is a direct approach to manipulate the electronic conductivity of LTO. However, doping may induce multiple effects influencing the overall electrochemical kinetics, e.g., changing the size of particles and the ionic and electronic conductivities. Here we systematically investigated the phase stability, electronic conductivity, and electrochemical kinetics of M-doped LTO (M = Na, K, Mg, Ca, Sr, Al, and Ga). With both ab initio calculations and experiments, the mechanism of electron transport within LTO is elucidated, the desired type of dopants for improving electronic conductivity of LTO is clarified, and the role of electronic conductivity in the electrochemical kinetics of LTO is revealed. These results provide an in-depth understanding of metal-doped LTO and would help the development of a variety of electrode materials. Graphical abstract: Image 1